A brief for fisheries policy research in developing countries - Ahmed, Mahfuzuddin; Delgado, Christopher L.; Sverdrup-Jensen, Sten (International Center for Living Aquatic Resources Management, 1997)
This brief explains the rationale behind and significance of carrying out fisheries research in developing countries. It suggests methods for setting policy priorities, reviews research issues, and recommends topics for policy research.